In vitro anti-diabetic activities and chemical analysis of polypeptide-k and oil isolated from seeds of Momordica charantia (bitter gourd) - Ahmad, Zuraini; Zamhuri, Khairul Faizi; Yaacob, Azhar; Chiong, Hoe Siong; Selvarajah, Malarvili; Ismail, Amin; Abdullah, Muhammad Nazrul Hakim (MDPI, 2012)
The amino acid and fatty acid composition of polypeptide k and oil isolated from the seeds of Momordica charantia was analysed. The analysis revealed polypeptide k contained 9 out of 11 essential amino acids, among a total of 18 types of amino acids. Glutamic acid, aspartic acid, arginine and glycine were the most abundant (17.08%, 9.71%, 9.50% and 8.90% of total amino acids, respectively). Fatty acid analysis showed unusually high amounts of C18-0 (stearic acid, 62.31% of total fatty acid). C18-1 (oleic acid) and C18-2 (linoleic acid) were the other major fatty acid detected (12.53% and 10.40%, respectively). The oil was devoid of the short fatty acids (C4-0 to C8-0). Polypeptide k and oil were also subjected to in vitro α-glucosidase and α-amylase inhibition assays. Both polypeptide k and seed oil showed potent inhibition of α-glucosidase enzyme (79.18% and 53.55% inhibition, respectively). α-Amylase was inhibited by 35.58% and 38.02%, respectively. Collectively, the in vitro assay strongly suggests that both polypeptide k and seed oil from Momordica charantia are potent potential hypoglycemic agents.